Islamic Financial Services Act 2013: A Preliminary Review on Its Impacts to Takaful Industry: (Akta Perkhidmatan Kewangan Islam 2013: Tinjauan Awal Kesannya dalam Industri Takaful) (Kanun: Jurnal Undang-undang Malaysia, 2014)
Islamic Financial Services Act 2013 (IFSA) has come into force on 30 June 2013 and it repeals the previous Takaful Act 1984 which has been the backbone of takaful industry for almost thirty years. IFSA aims to promote financial stability and compliance with shariah, in line with the expectation of public as consumers and subscribers of shariah compliant products. The enforcement of IFSA brings various impacts to takaful industry. In light of this background, this article attempts to analyse the salient impacts of IFSA to takaful industry. Based on the provisions of IFSA, takaful industry is currently facing with many challenges to ensure the statutory requirements are met without neglecting the shariah compliant aspect of the operations and activities of takaful operators.Keywords: takaful, shariah, Islamic Financial Services Act 2013, conditional hibah